Potassium polyacrylate gel electrolyte and preparation method and application thereof

By using a polypotassium acrylate gel electrolyte containing inorganic additives in the aluminum air battery, the problem of self-corrosion of the aluminum air battery is solved, the working voltage and energy density of the battery are improved, and the specific capacity and performance of the aluminum air battery are improved.

CN118299730BActive Publication Date: 2025-02-18HAIKOU QIANMU CONSULTING SERVICE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410543978.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-02-18
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

The actual discharge effect of aluminum air batteries is not ideal due to self-corrosion problems, the ionic conductivity of traditional quasi-solid electrolytes is not ideal, and although the alkaline gel electrolyte is excellent in ionic conductivity, it still cannot completely suppress the self-corrosion of the aluminum anode.

Method used

Potassium polyacrylate gel electrolyte containing inorganic additives is used to generate a smooth and flat metal film on the surface of the aluminum anode, preventing water molecules from contacting and inhibiting hydrogen evolution reaction, while not affecting the OH-participation reaction.

Benefits of technology

It effectively improves the working voltage and energy density of the aluminum air battery, inhibits the self-corrosion and hydrogen evolution reaction of the aluminum anode, and improves the specific capacity and performance of the aluminum air battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118299730B_ABST
    Figure CN118299730B_ABST
Patent Text Reader

Abstract

The present invention relates to a potassium polyacrylate gel electrolyte and a preparation method and application thereof, and the method comprises: preparing a potassium acrylate solution with acrylic acid and potassium hydroxide; dissolving the potassium acrylate solution with ammonium persulfate, N,N'-methylenebisacrylamide, and tetramethylethylenediamine in water, and adding a metal salt corresponding to a metal with a hydrogen evolution overpotential V>1.0 as an inorganic additive to form a mixed solution, and condensing the mixed solution into a potassium polyacrylate gel by polymerization reaction in a mold; soaking the potassium polyacrylate gel in an electrolyte solution, taking it out and drying it, and obtaining a potassium polyacrylate gel electrolyte. The potassium polyacrylate gel electrolyte prepared by the method of the present invention has a greatly improved ionic conductivity due to the presence of potassium hydroxide, and can effectively improve the operating voltage and energy density of an aluminum air battery; the materials used are all purchased commercially, and are easy to operate, low in production cost, and convenient for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aluminum-air batteries, and in particular to a potassium polyacrylate gel electrolyte and a preparation method and application thereof. Background Art

[0002] Aluminum-air batteries are promising candidates for the next generation of high-energy-density electrochemical energy sources, but their inherent defects hinder their practical application. Aqueous alkaline aluminum-air batteries have serious self-corrosion problems, resulting in unsatisfactory actual discharge performance of the battery. Hydrogel materials are quasi-solid electrolytes with high ionic conductivity that can solve the above problems. However, conventional quasi-solid electrolytes are not suitable for aluminum-air batteries because of their unsatisfactory ionic conductivity.

[0003] At present, alkaline gel electrolytes have attracted more and more attention due to their excellent ionic conductivity, which is close to solution-level conductivity. However, alkaline gel electrolytes still cannot completely inhibit the self-corrosion of aluminum anodes. Therefore, there is an urgent need to solve this problem. Summary of the invention

[0004] Based on the above problems, the present invention provides a potassium polyacrylate gel electrolyte and a preparation method and application thereof. In view of the self-corrosion problem of aluminum-air batteries currently using alkaline gel electrolytes, a potassium polyacrylate gel electrolyte containing inorganic additives is proposed. The potassium polyacrylate gel electrolyte can prevent water molecules from contacting the surface of the aluminum anode and form a smooth metal film on the surface of the aluminum anode, thereby inhibiting the hydrogen evolution reaction and not affecting the OH - Participate in the reaction, thus solving the technical problem of low utilization rate of aluminum-air battery anode.

[0005] To achieve the above object, the present invention provides a method for preparing a potassium polyacrylate gel electrolyte, which comprises the following steps:

[0006] S1, preparing a potassium acrylate solution by mixing acrylic acid and potassium hydroxide in a molar ratio of 1:0.1-1:2.0;

[0007] S2, completely dissolving the potassium acrylate solution obtained in step S1, ammonium persulfate, N,N'-methylenebisacrylamide, and tetramethylethylenediamine in water at a mass ratio of 5.0-30:0.5:0.05:0.05 to obtain a mixed solution A;

[0008] S3, using a metal salt corresponding to a metal with a hydrogen evolution overpotential V>1.0 as an inorganic additive, adding the inorganic additive to the mixed solution A at a molar concentration of 1.0-300.0 mM to obtain a mixed solution B;

[0009] S4, pouring the mixed solution B obtained in step S3 into a mold to obtain potassium polyacrylate hydrogel through polymerization reaction;

[0010] S5, dissolving an electrolyte in water to prepare an electrolyte solution, wherein the electrolyte is at least one of sodium hydroxide and potassium hydroxide; soaking the potassium polyacrylate hydrogel obtained in step S4 in the electrolyte solution for a period of time and then taking it out to obtain a potassium polyacrylate gel electrolyte.

[0011] As a further preferred technical solution of the present invention, step S1, step S2, step S3 and step S5 are all carried out at room temperature.

[0012] As a further preferred technical solution of the present invention, in step S1, step S2, step S3 and step S5, the solution is mixed by stirring, ultrasound or oscillation, and the mixing time is 0.1-24h.

[0013] As a further preferred technical solution of the present invention, the inorganic additive is one or more of zinc oxide, zinc acetate, zinc sulfate, zinc chloride, sodium stannate, and potassium stannate.

[0014] As a further preferred technical solution of the present invention, the concentration of the electrolyte in the electrolyte solution is 0.5-10.0M.

[0015] According to another aspect of the present invention, the present invention also provides a potassium polyacrylate gel electrolyte, which is prepared by the above method.

[0016] According to another aspect of the present invention, the present invention also provides an application of potassium polyacrylate gel electrolyte in an aluminum-air battery.

[0017] The potassium polyacrylate gel electrolyte of the present invention and its preparation method and application, by adopting the above technical scheme, can achieve the following beneficial effects:

[0018] The method of the present invention selects a potassium acrylate solution prepared by potassium hydroxide and acrylic acid as a monomer of the hydrogel, and at the same time, selects a metal salt corresponding to a metal with a relatively high hydrogen evolution overpotential (V>1.0) as an inorganic additive, and adds the inorganic additive to the hydrogel by an integrated molding method, and then forms a potassium polyacrylate gel electrolyte (also called an alkaline gel electrolyte containing an inorganic additive) by immersing it in an electrolyte solution.

[0019] The potassium polyacrylate gel electrolyte prepared by the method of the present invention has a greatly improved ion conductivity due to the presence of potassium hydroxide, which can effectively improve the operating voltage and energy density of the aluminum-air battery. In addition, there are a large number of hydrophilic -NH2 groups in the potassium polyacrylate gel electrolyte, which can form hydrogen bonds with active water, reduce the proportion of active water in the gel electrolyte, and inhibit the self-corrosion and hydrogen evolution reaction on the surface of the aluminum anode. At the same time, with the addition of inorganic additives, the specific capacity of the aluminum-air battery has been greatly improved. This is mainly because the metal ions can form complexes with -NH2 and migrate to the surface of the aluminum anode through the rich cross-linked network in the hydrogel matrix to form a metal deposition layer, covering the hydrogen evolution active sites on the surface of the aluminum anode, and preventing water molecules from contacting the surface of the aluminum anode, which more effectively inhibits the self-corrosion of the aluminum anode.

[0020] The potassium polyacrylate gel electrolyte of the present invention is applied to aluminum-air batteries, and can better inhibit the self-corrosion and hydrogen evolution reaction of the aluminum anode through the synergistic effect between the hydrogel matrix and the inorganic additive, thereby improving the performance of the aluminum-air battery.

[0021] The materials used in the method of the present invention are all purchased commercially, and the operation is simple, the production cost is low, and it is convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0023] Figure 1 This is a constant current discharge test curve of an aluminum-air battery based on a liquid electrolyte;

[0024] Figure 2 The constant current discharge test curve of the aluminum-air battery based on the alkaline gel electrolyte of Comparative Example 1;

[0025] Figure 3 It is a constant current discharge test curve of the aluminum-air battery based on the alkaline gel electrolyte of Comparative Example 2;

[0026] Figure 4 The constant current discharge test curve of the aluminum-air battery based on the alkaline gel electrolyte of Comparative Example 3;

[0027] Figure 5 This is a constant current discharge test curve of an aluminum-air battery based on the alkaline gel electrolyte of Example 1;

[0028] Figure 6 This is a constant current discharge test curve of an aluminum-air battery based on the alkaline gel electrolyte of Example 2;

[0029] Figure 7This is a constant current discharge test curve of an aluminum-air battery based on the alkaline gel electrolyte of Example 3;

[0030] Figure 8 This is a constant current discharge test curve of an aluminum-air battery based on the alkaline gel electrolyte of Example 4;

[0031] Fig. 9 This is a constant current discharge test curve of an aluminum-air battery based on the alkaline gel electrolyte of Example 5;

[0032] Fig.10 Scanning electron micrographs of aluminum anodes in aluminum-air batteries assembled based on (a) liquid electrolyte, (b) comparative example 3, (c) example 1, and (d) example 5 alkaline gel electrolyte.

[0033] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0034] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0035] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0036] Comparative Example 1

[0037] The potassium polyacrylate gel electrolyte without inorganic additives for aluminum-air batteries is prepared by the following specific steps:

[0038] A potassium acrylate solution is prepared according to a molar ratio of acrylic acid to potassium hydroxide of 1:0.5;

[0039] Potassium acrylate solution, ammonium persulfate, N,N'-methylenebisacrylamide and tetramethylethylenediamine are dissolved in water at a mass ratio of 10:0.5:0.05:0.05, mixed evenly and placed in a mold, and heated at a constant temperature in an oven to polymerize into a gel, thereby preparing a hydrogel without inorganic additives;

[0040] 50.0 mL of electrolyte solution was prepared from a solvent (water) and an electrolyte (sodium hydroxide), wherein the concentration of NaOH was 4.0 M; the hydrogel containing no inorganic additives was soaked in the electrolyte solution for 12 hours and then taken out to obtain a potassium polyacrylate gel electrolyte containing no inorganic additives.

[0041] Comparative Example 2

[0042] The potassium polyacrylate gel electrolyte for aluminum-air batteries without inorganic additives is prepared, which is different from Comparative Example 1 in that the potassium acrylate solution is prepared with acrylic acid and potassium hydroxide in a molar ratio of 1:2.0. The remaining steps are the same as those in Comparative Example 1.

[0043] Comparative Example 3

[0044] The potassium polyacrylate gel electrolyte without inorganic additives for aluminum-air batteries is prepared, which is different from Comparative Example 1 in that potassium acrylate solution, ammonium persulfate, N,N'-methylenebisacrylamide and tetramethylethylenediamine are dissolved in water at a mass ratio of 20:0.5:0.05:0.05 to prepare a hydrogel without inorganic additives. The remaining steps are the same as Comparative Example 1.

[0045] Example 1

[0046] The potassium polyacrylate gel electrolyte is prepared by the following steps:

[0047] A potassium acrylate solution is prepared according to a molar ratio of acrylic acid to potassium hydroxide of 1:0.5;

[0048] Potassium acrylate solution, ammonium persulfate, N,N'-methylenebisacrylamide and tetramethylethylenediamine are dissolved in water at a mass ratio of 20:0.5:0.05:0.05, mixed evenly, and zinc oxide with a concentration of 10.0 mM is added, placed in a mold, and heated at a constant temperature in an oven to polymerize into a gel, thereby preparing potassium polyacrylate gel;

[0049] 50.0 mL of electrolyte solution was prepared from a solvent (water) and an electrolyte (sodium hydroxide), wherein the concentration of NaOH was 4.0 M; potassium polyacrylate gel was soaked in the electrolyte solution for 12 hours and then taken out to obtain a potassium polyacrylate gel electrolyte containing an inorganic additive.

[0050] Example 2

[0051] The potassium polyacrylate gel electrolyte was prepared in the same manner as in Example 1, except that the concentration of zinc oxide was 20.0 mM. The remaining steps were the same as in Example 1.

[0052] Example 3

[0053] A potassium polyacrylate gel electrolyte was prepared, and the preparation method was basically the same as that of Example 1, except that the inorganic additive was replaced with zinc chloride with a concentration of 20.0 mM, and the concentration of NaOH in the electrolyte solution was set to 5.0 M. The remaining steps were the same as those of Example 1.

[0054] Example 4

[0055] A potassium polyacrylate gel electrolyte was prepared, and its preparation method was basically the same as that of Example 1, except that the inorganic additive was replaced with zinc sulfate with a concentration of 50.0 mM, and the electrolyte solution was prepared with KOH at a concentration of 5.0 M. The remaining steps were the same as those of Example 1.

[0056] Example 5

[0057] A potassium polyacrylate gel electrolyte was prepared by a method substantially the same as that of Example 1, except that the inorganic additive was replaced with potassium stannate at a concentration of 300.0 mM, and the electrolyte solution was prepared with KOH at a concentration of 10.0 M. The remaining steps were the same as those of Example 1.

[0058] The potassium polyacrylate gel electrolytes without inorganic additives prepared in Comparative Examples 1-3 and the potassium polyacrylate gel electrolytes with inorganic additives prepared in Examples 1-5 (hereinafter referred to as alkaline gel electrolytes) were assembled into aluminum-air batteries, and then, respectively, at 5 mA cm -2 Perform a constant current discharge test as follows:

[0059] The aluminum-air battery assembled with liquid electrolyte (4M NaOH solution) was used as the experimental control group. The constant current discharge test curve based on the liquid electrolyte is as follows: Figure 1 .

[0060] Figures 2 to 9 They are respectively the constant current discharge test curves of the alkaline gel electrolytes prepared based on Comparative Examples 1-3 and Examples 1-5. It can be seen that compared with the liquid electrolyte, the discharge specific capacity of the alkaline gel electrolyte is improved to a certain extent. This is due to the reduction in the proportion of active water in the alkaline gel electrolyte, which inhibits the self-corrosion and hydrogen evolution reaction on the surface of the aluminum anode. It can be seen from Comparative Examples 1-3 that with the increase in the content of potassium acrylate monomer in the alkaline gel electrolyte, the voltage and discharge specific capacity are improved to a certain extent. Comparing Examples 1-5 with Comparative Examples 1-3, it can be seen that with the addition of inorganic additives, the specific capacity of the aluminum-air battery has been improved to a greater extent. This is mainly due to the formation of a dense and stable metal deposition layer on the surface of the aluminum anode, which covers the hydrogen evolution active sites on the surface of the aluminum anode, prevents water molecules from contacting the surface of the aluminum anode, and more effectively inhibits the self-corrosion of the aluminum anode. Among them, such as Figure 5 , 6 It can be seen that the discharge capacity of the aluminum-air battery increases with the increase of the content of inorganic additives, because the inorganic additives with higher content can form a more stable metal deposition layer on the surface of the aluminum anode. At the same time, combined with Examples 3-5, it can be seen that the increase of the electrolyte content and the inorganic additive content in the immersion solution can greatly improve the discharge performance of the aluminum-air battery, and the discharge capacity can reach 2677.83 mAh g -1(Example 5).

[0061] The aluminum-air batteries assembled with the above liquid electrolyte, comparative example 3, example 1 and example 5 alkaline gel electrolyte were compared. Fig.10 It can be seen from the scanning electron microscope that the surface of the aluminum anode in the liquid electrolyte is uneven and full of cracks. The morphology of the aluminum anode surface of the alkaline gel electrolyte without inorganic additives is improved, while the surface of the aluminum anode of the alkaline gel electrolyte containing inorganic additives is smooth and flat, indicating that the metal deposition layer generated on the surface of the aluminum anode is very dense and stable, which can achieve the purpose of slowing down the self-corrosion of the aluminum anode. Preferably, among all the ratios, the alkaline gel electrolyte containing potassium stannate (300.0mM) is the best, and the corresponding discharge capacity is as high as 2677.83mAh g -1 .

[0062] In summary, the present invention uses a potassium polyacrylate gel electrolyte prepared by adding an inorganic additive to a potassium polyacrylate gel. The synergistic effect between the hydrogel and the inorganic additive can effectively inhibit the hydrogen evolution reaction, solve the problem of aluminum anode utilization of aluminum-air batteries, and improve the discharge specific capacity of aluminum-air batteries. The test results of the above embodiments fully prove that the alkaline gel electrolyte containing an inorganic additive can inhibit the hydrogen evolution reaction, thereby improving the performance of aluminum-air batteries.

[0063] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a potassium polyacrylate gel electrolyte, characterized in that: The following steps are involved: S1, preparing a potassium acrylate solution by mixing acrylic acid and potassium hydroxide in a molar ratio of 1:0.1-1:2.0; S2, completely dissolving the potassium acrylate solution obtained in step S1, ammonium persulfate, N, N'-methylenebisacrylamide, and tetramethylethylenediamine in water at a mass ratio of 5.0-30:0.5:0.05:0.05 to obtain a mixed solution A; S3, using a metal salt corresponding to a metal with a hydrogen evolution overpotential V>1.0 as an inorganic additive, adding the inorganic additive to the mixed solution A at a molar concentration of 1.0-300.0 mM to obtain a mixed solution B; S4, pouring the mixed solution B obtained in step S3 into a mold to obtain potassium polyacrylate hydrogel through polymerization reaction; S5, using at least one of sodium hydroxide and potassium hydroxide as an electrolyte, dissolving the electrolyte in water to prepare an electrolyte solution, soaking the potassium polyacrylate hydrogel obtained in step S4 in the electrolyte solution for a period of time and then taking it out to obtain a potassium polyacrylate gel electrolyte; wherein, The inorganic additive is one or more of zinc oxide, zinc acetate, zinc sulfate, zinc chloride, sodium stannate, and potassium stannate.

2. The method for preparing a potassium polyacrylate gel electrolyte according to claim 1, wherein Step S1, step S2, step S3 and step S5 are all performed at room temperature.

3. The method for preparing the potassium polyacrylate gel electrolyte according to claim 1, characterized in that: In step S1, step S2, step S3 and step S5, the solutions are mixed by stirring, ultrasound or oscillation, and the mixing time is 0.1-24 h; the soaking time in step S5 is 1-24 h.

4. The method for preparing the potassium polyacrylate gel electrolyte according to claim 1, characterized in that: The concentration of the electrolyte in the electrolyte solution is 0.5-10.0 M.

5. A potassium polyacrylate gel electrolyte, characterized in that: The method is prepared by any one of claims 1 to 4.

6. Use of the potassium polyacrylate gel electrolyte prepared according to the method according to any one of claims 1 to 4 in aluminum-air batteries.

Citation Information

Patent Citations

  • All-solid-state separable aluminium-air cell

    CN103515676A

  • Membrane for hydrogen generation and method of forming same

    WO2022077064A1